Discovery Learning for Islamic Education Improvement: Evidence from Jambi Junior High School, Indonesia - Reza Wahyu Saputra; M. Tantowi (Tunjuk Ajar: Journal of Education and Culture, 2025)
Learning outcomes among students in Islamic Religious Education (IRE) and Character Education at Junior High School Students at State Junior High School (SMPN) 7 Jambi City remain suboptimal, with the majority of students failing to achieve the Minimum Mastery Criteria (MMC). This condition indicates the necessity for innovative pedagogical models that can enhance students’ active engagement and foster profound conceptual understanding. This study aims to analyze the implementation of the discovery learning model in IRE and Character Education instruction and its impact on improving student learning outcomes. The research employed a Classroom Action Research (CAR) design conducted over two cycles with ninth-grade students at SMPN 7 Jambi City, involving 32 participants. Each cycle encompassed planning, implementation, observation, and reflection phases. Data were collected through teacher and student observation sheets, learning outcome assessments, and documentation, subsequently analyzed descriptively using percentages and mean scores. The findings demonstrate enhanced teacher and student activities, progressing from “good” in Cycle I to “excellent” in Cycle II, accompanied by an increased percentage of students achieving MMC. These findings indicate that the implementation of discovery learning contributes positively to enhancing student engagement and learning outcomes in IRE and Character Education subjects. The contribution of this research lies in providing empirical evidence regarding the effectiveness of discovery learning within the context of religious education in secondary schools, which can serve as a reference for teachers, curriculum developers, and policymakers in designing more interactive and student-centered learning strategies.